2004
DOI: 10.1016/s0968-8080(04)24010-1
|View full text |Cite
|
Sign up to set email alerts
|

Misoprostol Alone for Early Medical Abortion in a Latin American Clinic Setting

Abstract: Misoprostol is being used widely by women throughout Latin America, often based on instructions passed along through friends, acquaintances or professionals who may have little information about safe and effective use. This paper presents the experience of a Latin American clinic working in a legally restrictive setting that offers misoprostol as one option to women seeking early pregnancy termination. Between February 2001 and June 2002, 3,225 women who attended the clinic chose to use misoprostol rather tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
31
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 17 publications
(29 reference statements)
1
31
0
1
Order By: Relevance
“…Studies from Brazil, Honduras, Mexico, Nicaragua, Peru and Puerto Rico illustrate that women obtain misoprostol either from pharmacies without a prescription or from physicians, who either prescribe or dispense it directly, 9,10,[12][13][14][15] and a recent report of the safe and effective use of misoprostol alone in a Latin American clinic found that women were satisfied using misoprostol alone, would use it again if they needed to terminate another pregnancy and would recommend it to a friend. 12 Because an in-depth understanding of women's experiences with medical abortion in different settings in the region would help providers and women to use it more safely and effectively, we carried out a qualitative study to collect information about women's experiences using misoprostol or methotrexate plus misoprostol under clinical supervision in Mexico, Colombia, Ecuador and Peru. This study does not capture the experiences of women who do not have clinical support and who use misoprostol on their own or with the help of partners, friends or family, probably the most common mode of use of medical abortion in the region.…”
mentioning
confidence: 99%
“…Studies from Brazil, Honduras, Mexico, Nicaragua, Peru and Puerto Rico illustrate that women obtain misoprostol either from pharmacies without a prescription or from physicians, who either prescribe or dispense it directly, 9,10,[12][13][14][15] and a recent report of the safe and effective use of misoprostol alone in a Latin American clinic found that women were satisfied using misoprostol alone, would use it again if they needed to terminate another pregnancy and would recommend it to a friend. 12 Because an in-depth understanding of women's experiences with medical abortion in different settings in the region would help providers and women to use it more safely and effectively, we carried out a qualitative study to collect information about women's experiences using misoprostol or methotrexate plus misoprostol under clinical supervision in Mexico, Colombia, Ecuador and Peru. This study does not capture the experiences of women who do not have clinical support and who use misoprostol on their own or with the help of partners, friends or family, probably the most common mode of use of medical abortion in the region.…”
mentioning
confidence: 99%
“…This cost differential was largely due to the additional follow-up visit that was required with MA. A previous study in a Latin American country where abortion was illegal documented a similar MA protocol involving two follow-up visits; providers seemed particularly eager to ensure that women had a complete abortion as soon as possible, 19 likely because of the fear that women might seek care at a different clinic if they had prolonged bleeding or other unexpected symptoms. Only one follow-up visit is the norm in settings where the method is approved.…”
Section: Discussionmentioning
confidence: 99%
“…Misoprostol used alone (with repeat intravaginal doses) for pregnancy termination in the first trimester has complete abortion rates of 88-93% in clinical studies, [10][11][12][13][14] although lower success rates have been documented in actual practice in one Latin American clinic. 15 Misoprostol is relatively inexpensive in comparison to other abortion methods, it does not require refrigeration and in many countries, it is available over the counter at pharmacies without a prescription. 16 For these reasons, misoprostol alone is an option for women seeking safe abortion in Latin America and other legally restricted settings.…”
mentioning
confidence: 99%
“…16 For these reasons, misoprostol alone is an option for women seeking safe abortion in Latin America and other legally restricted settings. 15,17,18 Many women in Latin America, Africa, and Asia have used misoprostol to induce abortions without guidance from health care providers. Interviews with women who sought care for perceived complications revealed that many of the women lacked information on what to expect, on how to determine if their abortion was complete, and whether and when to seek emergency care.…”
mentioning
confidence: 99%
See 1 more Smart Citation